UTILIZATION OF THE LIBRARY AS A LEARNING PLACE IN BUILDING A LITERACY CULTURE FOR STUDENTS OF STATE SENIOR HIGH SCHOOL 1 BANDAR SURABAYA, CENTRAL LAMPUNG REGENCY - Aulia Nur Arsica; Aghesna Rahmatika Kesuma; Irva Yunita (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2026)
The library at State Senior High School 1 Bandar Surabaya has a floor area of 150 square meters and features areas such as book shelves, reading tables, and a visitor registration desk, as well as a computer lab located near the library. In general, the library’s floor area meets national library standards. However, the collection size still falls short of the minimum standard 360 titles compared to the required minimum of 1,000 titles with a student population of 287. This study aims to analyze the use of the library as a learning space in developing a culture of literacy among students at SMA Negeri 1 Bandar Surabaya. This study used a qualitative approach, with data collection techniques through observation, interviews, and documentation. The results indicate that the library has been utilized as a source of information, a place for independent and group study, and a space for student literacy activities. This utilization is supported by the library's comfortable physical condition and the role of teachers in guiding students to utilize the library in the learning process. However, the research findings also indicate that library utilization remains at a functional stage, namely as a provider of learning resources and activity space, and has not yet fully developed into a literacy space that encourages critical thinking and in-depth information processing. Furthermore, limited technological facilities and policies restricting device use create a paradox: the library serves as a primary source of book-based literacy, but is not yet optimal in supporting students' digital literacy. Theoretically, this study contributes to strengthening the understanding that library utilization as a learning space is a process that depends not only on the availability of facilities, but also on the integration of physical space, learning activities, social interactions, and structured pedagogical support. These findings point to the development of a gradual model for school library utilization, moving from its basic function as an information provider to a more integrative role as an active and contextual literacy learning space. Thus, this research has implications for strengthening school-based literacy ecosystems by optimizing the library's role as a center for learning and developing students' literacy culture.